Shifting the Character of the Constitutional Court Decision Influenced by Political Constellation in Indonesia - Hastuti, Proborini (Constitutional Review, 2019)
Recently, the decisions of the Constitutional Court have become one of the focuses in the dynamics of Indonesian state administration. This research discusses the relevance of political constellation in Indonesia and its influence on the changing character of several constitutional court decisions from self-executing to non-self executing. This research aims to find out how the legal impact of shifting the character of the Constitutional Court?s decision in its implementation. This research is a normative study supported by a law, case and conceptual approach. The data used are secondary data, obtained by means of a literature research which is then arranged systematically and analyzed with qualitative analysis. From the results of the analysis it is known that the shift in the character in several decisions of the Constitutional Court was carried out as an effort to offset the political constellation in the legislators. The character shift is done in the hope that it can guarantee the execution of the Constitutional Court?s ruling and can be followed up on by the decision of the ruling. This shows that Constitutional Court judges are trying to find a legal breakthrough in the corridor of judicial activism to make an ideal constitutional review decision.